2017
DOI: 10.18632/oncotarget.20283
|View full text |Cite
|
Sign up to set email alerts
|

The influence of two functional genetic variants of GRK5 on tau phosphorylation and their association with Alzheimer's disease risk

Abstract: Our work explores the relationship between G protein-coupled receptor kinase-5 (GRK5) single nucleotide polymorphisms and Alzheimer's disease risk. We confirmed that GRK5 translocates from the cellular membrane to the cytosol in the hippocampus of Alzheimer's disease mice and that GRK5 deficiency promotes tau hyperphosphorylation, a hallmark of Alzheimer's disease pathology. Our results indicate that one functional variant, or mutant, of GRK5 (GRK5-Gln41Leu) decreased GRK5 translocation from the membrane to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…Subsequently, Zhao et al confirmed these results and also demonstrated that in the hippocampus of global GRK5-KO mice, the activity of both tau and GSK3β resulted increased and correlated with AD phenotype [ 81 ]. Finally, Zhang et al demonstrated that in aged amyloid precursor protein ( APP ) and presenilin 1 ( PSEN1 ) double transgenic mice (APP +/− /PS1 +/− ), the reduced levels of GRK5 on plasma membrane correlated with the onset of AD [ 82 ].…”
Section: Grk5 and Neurodegenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, Zhao et al confirmed these results and also demonstrated that in the hippocampus of global GRK5-KO mice, the activity of both tau and GSK3β resulted increased and correlated with AD phenotype [ 81 ]. Finally, Zhang et al demonstrated that in aged amyloid precursor protein ( APP ) and presenilin 1 ( PSEN1 ) double transgenic mice (APP +/− /PS1 +/− ), the reduced levels of GRK5 on plasma membrane correlated with the onset of AD [ 82 ].…”
Section: Grk5 and Neurodegenerative Diseasesmentioning
confidence: 99%
“…The importance of GRK5 in the pathogenesis of AD has also been suggested by studies in humans. In particular, genetic sequencing has identified two functional SNPs in the grk5 gene, rs2230345 (GRK5-Q41L) and rs2230349 (GRK5-arginine [R] 304 histidine [H]) that have been linked to AD risk [ 82 ]. Specifically, Zhang et al demonstrated in mice that the functional variant Q41L impaired the ability of GRK5 to translocate from the membrane to the cytoplasm and was associated with decreased levels of phosphorylated tau.…”
Section: Grk5 and Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased calcium concentration could activate Gq/G11 proteins/phospholipase C (PLC) pathway [ 22 ] which, in turn, could modify tau, making it more toxic. Both excessive calcium level and increased tau toxicity lead to neuronal death [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tau is a very soluble hydrophilic protein [29]. Full-length tau remains soluble in solution up to 10M before it can aggregate.…”
Section: The Tau Pathology Catalystmentioning
confidence: 99%